PERTANGGUNGJAWABAN PELAKU USAHA TERHADAP PAKAIAN BEKAS IMPOR DI KOTA DENPASAR BERDASARKAN UNDANG-UNDANG NO 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Merciana, Ni Putu Sienny; Ayu Darma Pratiwi, Agustina Ni Made (Jurnal Hukum Mahasiswa, 2024)
The business of trading fashion goods or used clothing is known nowadays as thrifting. Regulation of the Minister of Trade Number 40 of 2022 concerning Amendments to Regulation of the Minister of Trade Number 18 of 2021 concerning Goods Prohibited from Export and Goods Prohibited from Import. Where in Article 2 Paragraph 3 it is written that goods are prohibited from import, one of which is used bags, used sacks and used clothes. Here it is very clear regarding the regulations prohibiting the import of used clothes, but in reality there are still people selling used imported clothes in Denpasar City. The problem in this research is the responsibility of imported used clothing business actors who harm consumers based on Law Number 8 of 1999 concerning Consumer Protection as well as the government's role in overcoming the practice of buying and selling imported used clothing which can harm consumers. The method in this research is empirical legal research. The conclusion in this research is that business actors in imported used clothing tend to be irresponsible, where business actors should be held responsible from various legal aspects. Legal certainty is really needed by a consumer to guarantee all forms of rights in carrying out trading activities.